Relation of food intake to nutritional status of students in islamic boarding schools - Syarfaini Syarfaini; Ulfah Humaidah; Irviani Anwar Ibrahim (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Adolescence is a period of dramatic change in a person. This sudden increase in growth is accompanied by hormonal, cognitive and emotional changes. Teenagers really need more nutrients because of increased growth and physical development that is very drastic. This study aims to determine the relationship of food intake with the nutritional status of adolescent students of SMP Buq'atun Mubarakah Pondok Pesantren Darul Aman Makassar. This research method used quantitative analytic with cross sectional approach. Retrieval of food intake data used the food weighing method for 3 consecutive days. Determination of nutritional status was obtained from BMI/A parameters (body mass index/age). Statistical test results showed no relationship between energy intake, protein intake, vitamin A intake, iron, zinc and fat intake with the nutritional status of students, but we obtained a significant relationship between carbohydrate intake and nutritional status. In addition, we found no relationship between diarrheal infections and typhoid infections with nutritional status. We recommend that the pesantren can design a varied list of food menus for students to fulfill a balanced nutritional status